Por que rejeitar o reducionismo em ética?: falacia naturalista e superveniencia moral na obra de G. E. Moore - Fernando da Costa Cardoso (2007)
This dissertation aims, in the metaethical level, to investigate the question of the naturalization of Ethics in the work of G. E. Moore (1873-1958). Moore has developed an argument aimed to testthe truth of an naturalized ethics. His anwser, at his first book, Principia Ethica (1903), was negative because he sustained that every attempt to naturalize ethics implies in a mistake, the naturalistic fallacy, a fallacy which existence could be proved by the experiment of the openquestion argument. In answer to this, Moore developed and defended a non-naturalistic position in the ethical field. The difficults involved in this non-naturalistic conception of ethics nevertheless led him to review his initial position and to develop what could be view as a discovery : the supervenient character of the ethical properties over the natural properties. This is the path that the dissertation pretends to follow.